TRENDS, CHARACTERISTICS AND INCIDENCE OF ANAPHYLAXIS IN 2001–2010: A POPULATION BASED STUDY - Lee, Sangil (J Allergy Clin Immunol, 2016)
BACKGROUND: Anaphylaxis is a potentially life-threatening systemic allergic reaction. OBJECTIVE: We aimed to determine the incidence rate and causes of anaphylaxis during a 10-year period in Olmsted County, Minnesota. METHODS: Using the resources of the Rochester Epidemiology Project, a comprehensive records linkage system, we performed a population-based incidence study in Olmsted County, Minnesota, from 2001 through 2010. All cases with a diagnosis of anaphylactic shock and 20% of cases with related diagnoses were manually reviewed. The relationships of age group, sex, and year of anaphylaxis with incidence rates were assessed by fitting Poisson regression models. RESULTS: Six hundred and thirty-one cases of anaphylaxis were identified. Median age was 31 years (interquartile range 19–4). The overall age- and sex-adjusted incidence rate was 42 (95% CI 38.7–45.3) per 100,000 person-years. There was a significant increase in the overall incidence of anaphylaxis during the study period with an average increase of 4.3% per year (P < 0.001). In addition, there was a 9.8% increase per year in the incidence rate for food-related anaphylaxis. Food-related anaphylaxis was most common in children aged 0–9 years, venom related anaphylaxis was most common in those 20–39 years of age, and medication-related anaphylaxis was most common in those 30–39 years of age. CONCLUSION: The overall incidence rate of anaphylaxis was 42 per 100,000 person-years from 2001–2010 in Olmsted County, Minnesota. The incidence of anaphylaxis increased over time, and several inciting triggers were uniquely associated with different age groups.